THE USE OF VLOGGING TO ENHANCE SPEAKING PERFORMANCE OF ESL STUDENTS IN A MALAYSIAN SECONDARY SCHOOL - Shoba, Andiappan; Goh, Hock Seng; Soo, Ruey Shing (2022)
This study investigates the effect of a vlogging project on Malaysian ESL students’ speaking performance in a secondary school. Additionally, the students’ experience and perception of making and using vlogs in their language learning were also investigated. To this end, a mixedmethods approach was adopted and the data was collected from 73 participants. A quasiexperiment was conducted to determine the effect of the vlogging project while a questionnaire and a retrospective self-report were utilised to obtain the participants’ views pertaining to their experience in creating vlogs. The findings indicate statistically significant improvement in the ESL students’ speaking scores. Additionally, the participants viewed the vlogging project positively and perceived it as a student-friendly learning tool which can also promote selfevaluation and function as a source of motivation. Drawing on the findings, ESL teachers should consider the pedagogical benefits of vlogs and incorporate them as an instructional technique in the language classrooms. This study indicates that the use of vlogs warrants further research in order to inform the feasibility and pedagogical impact of using vlogs to enhance students’ speaking skills.